2014
DOI: 10.1080/10934529.2014.859453
|View full text |Cite
|
Sign up to set email alerts
|

Low-heat, mild alkaline pretreatment of switchgrass for anaerobic digestion

Abstract: This study examines the effectiveness of alkaline pretreatment under mild heat conditions (100°C or 212°F) on the anaerobic co-digestion of switchgrass. The effects of alkaline concentration, types of alkaline, heating time and rinsing were evaluated. In addition to batch studies, continuous-feed studies were performed in triplicate to identify potential digester operational problems caused by switchgrass co-digestion while accounting for uncertainty due to digester variability. Few studies have examined anaer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Breaking these polymers into sugars requires strict and costly pretreatment to improve hydrolysis, as well as to minimize carbohydrate losses and avoid by-product inhibition, making the switchgrass-toethanol process not competitive in terms of economic efficiency [13,14]. However, the anaerobic bacteria are able to produce methane from a wide array of compounds, not just sugars, and appear to be far more tolerant of inhibitory compounds [15,16]. Therefore, switchgrass may be a more promising feedstock for biogas production than for ethanol production in terms of the effective breakdown and economic conversion of lignocelluloses.…”
Section: Introductionmentioning
confidence: 97%
“…Breaking these polymers into sugars requires strict and costly pretreatment to improve hydrolysis, as well as to minimize carbohydrate losses and avoid by-product inhibition, making the switchgrass-toethanol process not competitive in terms of economic efficiency [13,14]. However, the anaerobic bacteria are able to produce methane from a wide array of compounds, not just sugars, and appear to be far more tolerant of inhibitory compounds [15,16]. Therefore, switchgrass may be a more promising feedstock for biogas production than for ethanol production in terms of the effective breakdown and economic conversion of lignocelluloses.…”
Section: Introductionmentioning
confidence: 97%
“…Most studies have focused on these operating factors over a wide range of temperatures (0-200°C), times (10 min to 21 d), SLRs (1:0. 8-1:19) and ALRs (1-152%) [14][15][16][17][18][19]. In general, pretreatment increases methane production (from 0% to 174.2%) from LB compared with untreated samples [13,[20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has shown that the release of lignin-derived monomers during alkaline pretreatment is time dependent and maximum release occurs around 30–40 min. , Therefore, in this work, we chose to investigate pretreatment conditions at high temperatures (≥100 °C) and short residence times of 30 min at temperature to maximize the concentration of monomeric lignin-derived species in the APL. However, alkaline pretreatment of switchgrass at temperatures lower than and sodium hydroxide loadings similar to those reported here have been found to remove up to 85.8% of the lignin present but only with much longer residence times (>10 h). These longer pretreatments allow sufficient time for additional reactions to occur within the APL that increase its average molecular weight, which may not be optimal for a feed stream for downstream biological upgrading . However, one could envision extending the analysis in Figure along an additional dimension of pretreatment time given a complete data set of pretreatment time on the resulting composition of the recovered solids.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, ionic liquid pretreatment has received significant attention given the ability for some ionic liquids to solubilize cellulose, lignin, or whole biomass. , Base-catalyzed pretreatments are also popular and are being scaled-up for industrial use. The well-studied ammonia fiber expansion (AFEX) approach, which solubilizes a fraction of primary plant cell wall components, is able to render biomass quite digestible by fungal cellulases, likely by increasing cell wall porosity. ,, Other alkaline approaches include alkaline pretreatment with sodium hydroxide and alkaline peroxide (the latter using a combination of NaOH and H 2 O 2 ), which aim to remove lignin from biomass and retain polysaccharides for subsequent downstream depolymerization. The economics for cellulosic ethanol production using several leading pretreatment technologies were compared by a large consortium of investigators and were found to be reasonably similar in cost and overall yield (when enzymatic hydrolysis is included) of fermentable sugars. , …”
Section: Introductionmentioning
confidence: 99%